Structural, Thermal and Film forming properties of Gelatin from Pink Perch Surimi Refiner Discharge - Hanjabam, M. D.; Balange, A. K.; Zynudheen, A. A. (Fishery Technology, 2017)
The objective of the present study was to characterizethe gelatin obtained from pink perch (Nemipterusjaponicus) surimi refiner discharge [referred asrefiner discharge gelatin (RDG)] with reference toits structural, thermal and film forming ability.Fourier transform infrared (FTIR) and DifferentialScanning Calorimetry (DSC) techniques were usedto characterize the gelatin. An edible film wasdeveloped with different concentrations of RDG(2-6%) by casting method. FTIR analysis showedthat the gelatin from refiner discharge has similarspectra with porcine gelatin (PG). The amide I andamide II bands of RDG occurred at around 1654 and1578 cm-1 respectively. RDG has a broad endothermicpeak at 85.64oC with transition enthalpy (Î”H)of 208.02 J g-1 as revealed by thermal analysisindicating the thermal transition temperature andthe energy required for the transition respectively.RDG showed good film forming property. Thegelatin concentration had strong significant (p